A Comparison between English and Makassarese Politeness System: A Comparative Study - Nurjannah Syarifuddin; Abdul Hakim Yassi; Harlinah Sahib (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
This study aimed to describe the dominant variable that affected in use of politeness systems and to analyse the process of native speakers of English and Makassar in using the politeness system through conversations. The method of this study was the quantitative method and used statistic frequency. In this study, there are two variables that affected politeness. These data were processed based on the identification, classification, description, grouping, and calculation. Yassi’s theoretical framework found there are six politeness strategies. The strategies are deference in non-kinship, deference in kinship, intimacy in non-kinship, intimacy in kinship, hierarchy in non-kinship, and hierarchy in kinship. Based on his theory, age and seniority were the most affected in use politeness. The researcher found the difference in this study. The research finding indicates that the two variables do not affected the politeness systems of English but it is affected for Makassarese politeness systems. The English and Makassarese were different countries, so the politeness systems were also different. The English used FTA in doing communications and Makassarese has positive and negative politeness. The educational background is the dominant variable in use negative politeness and the age affect in use positive politeness for Makassarese.